Thriving, surviving, or going under : coping with everyday lives - Frydenberg, Erica, 1943- (Emerald Publishing Limited : Information Age Pub., 2004)
Schools are increasingly being called upon to aid in the development of resilience in young people in order to be proactive and prevent the consequences of poor social-emotional health and well-being. In this collection of 13 essays, 19 scholars from Australia, the UK, Israel, and the U.S. offer current theory and research on coping by young people, and its application to the educational setting. Coverage includes an overview of coping and coping strategies; resources and coping with prevalent problems, such as anxiety and aggression; teaching coping skills; coping strategies for parents; and teacher training for low-burnout teaching.
Keywords: Adjustment (Psychology) in adolescence.; Child rearing.; Educational psychology.; Education -- Teaching -- Subjects -- Health & Sexuality.; Counselling and care of students.; Teaching of a specific subject.; Educational: Personal and health education.; elektronické knihy; electronic books